Evaluation of Bone Marrow Biopsy in Pancytopenia-An Institutional Understanding - Swain, Rati Ranjan; Sahoo, Sandhya Rani; Sethy, Sudha; Mohanty, Pranati (Medicine and Medical Research: New Perspectives Vol. 12, 2024)
Background: Pancytopenia is not a disease entity, but a triad of findings, resulting from various disease processes. It is characterized by anaemia, leucopenia and thrombocytopenia in the peripheral blood. It is a relatively common phenomenon in daily medical practice and one of the most common reasons for consultation from hematologists. Bone marrow examination is of utmost importance in the evaluation of pancytopenia and thereby identification of the disease process is helpful for appropriate management. Aims: The aim of the study is to analyse a wide spectrum of haematological diseases giving rise to pancytopenia in bone marrow trephine biopsy. Materials and Methods: This was a prospective study conducted in the department of Pathology and Clinical Hematology, S.C.B. Medical College, Cuttack for a period of 2 years including 122 pancytopenia patients. Complete blood count including peripheral smear examination, followed by bone marrow aspiration (BMA) and trephine biopsy were carried out in all cases. A detailed study of bone marrow examination was done and diagnoses were established in all the pancytopenia cases. All the relevant data were compiled and analysed for further investigation and planning. Results: Pancytopenia often creates a diagnostic challenge for clinicians. Identification of the accurate cause is crucial in the management of these patients. Among 122 patients studied, 63.1% were males and 36.9% females. Aplastic anaemia was the commonest cause of pancytopenia (51%) followed by megaloblastic anaemia (23%). Other causes include acute leukaemia 9%, MDS 6%, primary myelofibrosis 2%, lymphomatous infiltration in the marrow 2%, and multiple myeloma 3%. Metastatic deposit, tuberculosis, haemophagocytic syndrome and hypersplenism constituted 1% each. Conclusion: BMA and biopsy were diagnostic in all the cases of pancytopenia. Though in a few cases, BMA yields a dry tap and inconclusive coupled with bone marrow biopsy (BMB) it helps in defining diagnostic and therapeutic strategies in pancytopenia. The present study concluded that the most common cause of pancytopenia is aplastic anaemia, followed by megaloblastic anaemia and acute leukemia.